2004
DOI: 10.1097/01.cad.0000131684.06390.fe
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic advantage of intra-arterial hepatic oxaliplatin administration: comparative results with cisplatin using a rabbit VX2 tumor model

Abstract: The aim of this study was to compare intra-arterial hepatic administration (IAH) versus i.v. administration of oxaliplatin and cisplatin in a VX2 tumor model in rabbits. VX2 tumors were implanted in the livers of White New Zealand female rabbits and 2 weeks later they received either cisplatin (4 mg/kg) or oxaliplatin (6 mg/kg) administered by IAH or i.v. Platinum pharmacokinetic parameters were measured by atomic absorption spectrometry at baseline, 2, 5 10, 20, 40 and 60 min, and then at 2, 4, 6 and 24 h aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 18 publications
1
49
0
1
Order By: Relevance
“…This good tolerance may have been caused by the higher hepatic clearance of oxaliplatin administered by HAI administration versus iv administration and the subsequently lower systemic exposure shown in an animal model. 53 However, previous publications in humans have reported relatively small variations in systemic exposure after HAI oxaliplatin 27 and a 42% to 48% incidence of neuropathy with HAI oxaliplatin. 27,29 Thus, multidrug chronomodulated HAI represents an active treatment modality for patients with metastatic CRC whose disease has become resistant to all intravenously active drugs.…”
Section: Discussionmentioning
confidence: 87%
“…This good tolerance may have been caused by the higher hepatic clearance of oxaliplatin administered by HAI administration versus iv administration and the subsequently lower systemic exposure shown in an animal model. 53 However, previous publications in humans have reported relatively small variations in systemic exposure after HAI oxaliplatin 27 and a 42% to 48% incidence of neuropathy with HAI oxaliplatin. 27,29 Thus, multidrug chronomodulated HAI represents an active treatment modality for patients with metastatic CRC whose disease has become resistant to all intravenously active drugs.…”
Section: Discussionmentioning
confidence: 87%
“…They reported OS and PFS of 11.7 and 8.1 months, respectively, with the gemcitabine-cisplatin combination, In France, based on phase II studies by Andre et al [16] and Lee et al [6], the gemcitabine-oxaliplatin combination is used preferentially as a first-line treatment for advanced-stage biliary tract carcinoma. The rationale to use HAI of oxaliplatin was obtained from pharmacological studies that demonstrated a favorable hepatic extraction of oxaliplatin after HAI and oxaliplatin concentration in the tumor [17,18]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, total body clearance and hepatic extraction of 5FU decreases at high doses (13). Although oxaliplatin does not have superior pharmacokinetic characteristics for HAI, e.g., a long half life (15 to 19 hours), differences were seen in tumor versus healthy hepatic tissue in a ratio of 4.3, suggesting that oxaliplatin could be administered effectively and with minimal toxicity via the intra-arterial route (14,15). Irinotecan is not suited for HAI as it is converted to an active metabolite, SN-38, in the liver after first-pass extraction, and systemic effects are seen.…”
Section: Rationale For Hepatic Arterial Infusion Of Floxuridinementioning
confidence: 99%